HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI TERHADAP PRILAKU PENANGANAN DISMENORE DI SMPN 1 WIH PESAM KABUPATEN BENER MERIAH - Simah Bengi, Seftia; Yusran, Mawadhah; HS, Nurlaely (Akper Kesdam I/Bukit Barisan Padang, 2024)
ABSTRACT Dysmenorrhea or dysmenorrhea in Indonesian means pain during menstruation. In BenerMeriah Regency, especially at SMP N 1 Wih Pesam which consists of 334 female students. Where only 20 of the 134 female students from grade 9 did not experience dysmenorrhea, 10 of the 99 female students from grade 8, and 7 of the 101 female students from grade 7. The rest experienced pain during menstruation or what we often call dysmenorrhea. This research aims to find out